Povezave med pravno ureditvijo varstva potrošnikov in konkurenčnim pravom - Sladič, Jorg (LeXonomica, 2011)
Links between consumer protection law and competition law. The aim of this paper is the research of common elements of competition law and consumer protection law. The author considers that private law is the common legal basis of both competition law and consumer protection law and develops a theory under which the protection of the autonomy of parties to a contract against illicit influence is the aim of rules on competition and consumer protection. The author suggests an analysis of the economic notion of information asymmetry as legal basis for both set of rules. Povzetek. Namen tega prispevka je iskanje skupnih elementov konkurenčnega prava in pravne ureditve varstva potrošnikov. Avtor meni, da je zasebno pravo temelj tako konkurenčnega prava kot tudi prava varstva potrošnikov, in razvije teorijo, da je varovanje avtonomije volje pred nedovoljenimi posegi bistvo konkurenčnega prava in pravne ureditve prava potrošnikov. Avtor predlaga analizo ekonomskega pojma informacijske asimetrije kot pravne podlage obeh pravnih ureditev.